Food Security and the Futures of Farmers in Decentralisation Era: a Case Study From Sigi District Central Sulawesi - Alamsyah, Muhammad Nur; Sultan, Sultan; Sayuti, Sayuti (Universitas Negeri Semarang, 2015)
Decentralization is a form of democratization used to push development at district level. The formation of new autonomous regions results into more land conversion and politicization of society, rather than the strengthening of food security and the wellbing of farmers. This study examines the effectivity of local policy of Sigi District South Sulawesi to strengthen food security and elevate the prosperity of farmers. Through qualitative methods to bring together stakeholders (farmers, local authorities) through focus group discussions and in-depth interviews, the study found that the district policy still is formalistic. There is no standard information dissemination,no better attitude and commitment to the policy, limited resources, and there is no work standard. The role of regional food security council is not optimal, a lot of institutional barriers, there is no involvement of the community in accessing the programmes and also high politicization of this top down policy. Key Word: Policy, Local Goverment, food security, DecentralizationDesentralisasi merupakan wujud demokratisasi daerah untuk pembangunan. Pembentukan daerah otonom baru (DOB) melahirkan terjadinya alih fungsi lahan dan politisasi masyarakat seperti petani daripada penguatan ketahanan pangan dan penguatan petani. Penelitian ini bertujuan meneliti kebijakan Kabupaten Sigi dalam hal penguatan ketahanan pangan dan petani. Melalui metode kualitatif dengan mempertemukan pemangku kepentingan (petani, pejabat daerah) melalui diskusi kelompok terfokus dan wawancara mendalam, diketahui bahwa kebijakan masih bersifat formalistik. Tidak ada sosialisasi informasi secara baik, sikap dan komitmen terhadap kebijakan kurang, keterbatasan sumber daya, tidak ada standar kerja. Dewan ketahanan pangan daerah belum optimal, hambatan struktur dan kelembagaan, tidak ada keterlibatan masyarakat dalam mengakses penyusunan program serta tingginya politisasi pada bidang pertanian yang semuanya dikelola secara top down di daerah.